Problems of definition of subjective symptoms of computer crime under the laws of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
This article discusses the main problem of the definition of subjective symptom computer crimes. Analyzesthe norms of the Criminal Code of the Republic of Kazakhstan regulating the fight against computer crime,and suggests ways to improve these standards by specifying the subject of the crime.Keywords: computer crime, guilt, motive, purpose, network, Internet, computer information, illegal.